Implikasi Hukum Kebijakan Vaksinasi di Indonesia: Analisis Studi Kasus Peredaran Vaksin Ilegal dan Palsu - Dielasy Budiarti; Dede Mahdiyah (Jurnal Riset Rumpun Ilmu Sosial, Politik dan Humaniora, 2025)
The COVID-19 pandemic has accelerated the vaccination program in Indonesia as an effort to mitigate the health crisis. However, this emergency has also opened up opportunities for the widespread circulation of illegal and counterfeit vaccines, threatening public safety. This article aims to analyze the legal implications of this phenomenon through a normative-empirical approach using case studies. Three main cases are analyzed: the 2016 national counterfeit vaccine case, the 2021 illegal COVID-19 vaccine sales case in North Sumatra, and the falsification of COVID-19 vaccine certificates that occurred between 2021 and 2022. The analysis focuses on identifying legal loopholes, weaknesses in the oversight system, and their consequences for human rights protection and the integrity of public health programs. The results show fragmented oversight of vaccine distribution, weak transparency in the vaccine supply chain, and legal sanctions that have not provided a significant deterrent effect on perpetrators of health crimes. These conditions not only threaten individual safety but also undermine public trust in the national vaccination program. Inconsistent law enforcement and weak inter-agency coordination have exacerbated the situation. Therefore, efforts are needed to strengthen stricter regulations, increase synergy between supervisory and law enforcement agencies, and secure an integrated and transparent health information system. These measures are expected to ensure the security of vaccine distribution and enhance the accountability of the vaccination program in Indonesia, thus optimally protecting the public's right to health.